(untitled) (Research, Society and Development, 2020)
This research consists of the evaluation of the rice husk ash (RHA) without controlled burning potential in the partial replacement of cement in the concrete fabrication. In an environmental context, the manufacture of cement makes the cement industry one of the largest emitters of carbon dioxide in the world. RHA is used in mortars and concretes, due to its pozzolanic property, with the objective of cement consume reduction in the concreto blends and, consequently, increase the sustainability of civil construction activities. The objective of this research consisted of 10%, 15% and 20% of cement (by weight) replacement by the RHA. Posteriorly, the RHA workability, the uniaxial compressive strength and the durability of the concrete were evaluated. The methodology consisted of an experimental program. Characterization tests of the RHA and the concrete constituent aggregates were carried out. Besides, structural viability of the concrete with RHA were evaluated. B.E.T and laser granulometry tests were carried out in the concrete with RHA and the cement. The RHA used in this research presented much larger particle size and specific surface area when compared with Portland cement. Due to this fact, the irregular surface and porosity of the RHA, the concrete with RHA had its workability affected in the fresh condition. Slumptest were carried out and the results were null for concretes with 10% and 15% of RHA. In case of default concrete trace, the result of slumptest was equal to 80 mm. The obtained results indicate that the RHA without controlled burning used in this research presents low pozollanic property. However, the specimens prepared with the RHA presented a percentage of uniaxial compressive strength gain at 28 days of age greater than the default concrete. At 56 days, the concrete trace with replacement of 10% of RHA achieved the characteristic strength adopted in the research. However, the result obtained was still below the characteristic strength of the default concrete. Regarding the durability tests, the specimens with the RHA presented higher water absorption content in all traces at 28 days of age. At 56 days of age, the concrete with 10 % of RHA presented a absorption reduction equal to 2.4% compared to the concrete at 28 days. At 56 days of age, the concrete with 15 % of RHA presented a absorption reduction equal to 1.79% compared to the concrete at 28 days. The results obtained related to the mechanical and durability properties of concrete with RHA without controlled burning are presented in this article in order to contribute to the dissemination of the use of this waste in the civil construction industry.